(untitled) (Bangladesh Journal of Agricultural Research, 2023)
Thirteen betelvine cultivars (PB 001 to PB 013) collected from different locations of Bangladesh showed remarkable variations in disease reaction to foot and root rot caused by Sclerotium rolfsii. The lowest incubation period 8 days was required for the cultivars PB 005 (BARI line), PB 006 (Misti pan), PB 009 (BARI Pan-1) and PB 010 (Bangla pan) and the highest incubation period 22 days was required for the cultivars PB 001 (Laldingi pan) and PB 013 (Gayasur pan) for appearance of 1st disease symptoms. The disease incidence ranged 8.33 to 100% at 30 days after inoculation. The lowest disease incidence was recorded in PB 001 (Laldingi pan), while the highest disease incidence was recorded from PB 002, PB 003 (Chalitaguti pan), PB 004 (Sanchi pan), PB 005, PB 006 (Misti pan), PB 007, PB 008, PB 009 (BARI Pan-1), PB 010 (Bangla pan) and PB 012 (Bhabna pan) followed by PB 011 (Jhal pan) and PB 013 (Gayasur pan). Based on incidence of foot and root rot on those cultivars, PB 001 (Laldingi) was graded as resistant, PB 011 (Jhal pan) and PB 013 (Gayasur pan) as moderately susceptible and rest of the cultivars as susceptible. Bangladesh J. Agril. Res. 46(1): 63-69, March 2021